Bilateral Hemispheric Processing of Words and Faces: Evidence from Word Impairments in Prosopagnosia and Face Impairments in Pure Alexia. (18th December 2012) - Behrmann, Marlene; Plaut, David C.
Abstract : Considerable research has supported the view that faces and words are subserved by independent neural mechanisms located in the ventral visual cortex in opposite hemispheres. On this view, right hemisphere ventral lesions that impair face recognition (prosopagnosia) should leave word recognition unaffected, and left hemisphere ventral lesions that impair word recognition (pure alexia) should leave face recognition unaffected. The current study shows that neither of these predictions was upheld. A series of experiments characterizing speed and accuracy of word and face recognition were conducted in 7 patients (4 pure alexic, 3 prosopagnosic) and matched controls. Prosopagnosic patients revealed mild but reliable word recognition deficits, and pure alexic patients demonstrated mild but reliable face recognition deficits. The apparent comingling of face and word mechanisms is unexpected from a domain-specific perspective, but follows naturally as a consequence of an interactive, learning-based account in which neural processes for both faces and words are the result of an optimization procedure embodying specific computational principles and constraints.